2016
DOI: 10.1016/j.celrep.2016.07.017
|View full text |Cite|
|
Sign up to set email alerts
|

Feedback Loop Regulation of SCAP/SREBP-1 by miR-29 Modulates EGFR Signaling-Driven Glioblastoma Growth

Abstract: Summary Dysregulated lipid metabolism is a characteristic of malignancies. Sterol regulatory element-binding protein-1 (SREBP-1), a transcription factor playing a central role in lipid metabolism, is highly activated in malignancies. Here, we unraveled a previously unappreciated link between miR-29 and the SCAP/SREBP-1 pathway in glioblastoma (GBM) growth. EGFR signaling enhances miR-29 expression in GBM cells via upregulation of SCAP/SREBP-1, and SREBP-1 activates miR-29 expression via binding to specific sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
67
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 41 publications
3
67
0
Order By: Relevance
“…Accumulating evidence has shown that SCAP/SREBPs play important roles in malignancies, connecting oncogenic signaling to lipid metabolism alterations, leading to rapid tumor growth (Figure 1) [13, 60, 61, 7678, 80, 82]. Multiple studies have suggested that SCAP/SREBPs are very promising molecular targets in cancer treatment.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Accumulating evidence has shown that SCAP/SREBPs play important roles in malignancies, connecting oncogenic signaling to lipid metabolism alterations, leading to rapid tumor growth (Figure 1) [13, 60, 61, 7678, 80, 82]. Multiple studies have suggested that SCAP/SREBPs are very promising molecular targets in cancer treatment.…”
Section: Resultsmentioning
confidence: 99%
“…We found that GBM tumors bearing amplified EGFR, or expressing EGFRvIII, the constitutively active form of the receptor that lacks a portion of the extracellular ligand-binding domain, were greatly dependent on SREBP-1-mediated lipid synthesis and uptake for rapid growth [61]. EGFR/EGFRvIII activates SREBP-1 through upregulation of PI3K/Akt signaling, promoting the expression of ATP citrate lyase (ACLY), acetyl-CoA carboxylase (ACC), fatty acid synthase (FASN), stearoyl-coenzyme A desaturase 1 (SCD1) and low density lipoprotein receptor (LDLR) to enhance fatty acid synthesis and cholesterol uptake [13, 60, 61, 80, 83]. …”
Section: Activation Of Scap/srebps In Cancermentioning
confidence: 99%
See 3 more Smart Citations